How to use the internet in ELT - Teeler, Dede (Longman, 2000)
"How to use the internet in ELT is a practical guide to the use of the internet for teachers of English. This book is appropriate for teachers who have little or no experience of the internet as well as for those looking to extend their understanding of the resources available on the 'Net" -- back cover.